Optimization of a regional distribution center location for parts of end-of-life vehicles. (July 2018) - Sun, Y; Wang, YT; Chen, C; Yu, B
The high transportation cost of the parts of end-of-life vehicles (ELVs) has received a great deal of attention lately, and different approaches for solving the problem have been taken. In this paper, a bi-level programming model is developed to decompose the distribution center location problem for the parts of ELVs in order to obtain a trade-off between the location cost of the distribution center and the transportation cost. The upper level determines the sites of distribution centers and the lower level represents the delivery routes under any location pattern of candidate sites of distribution centers. The proposed model is illustrated by real data and the results demonstrate that it can be an effective method to determinate a distribution center for ELVs.